Pharmacological and nonpharmacological approaches to hypertension treatment among veterans: a systematic review protocol - Oleksandr Svyntozelskyi; Olesia Nasonenko (Systematic Reviews)
Abstract Background Hypertension (HTN) is the leading cause of mortality worldwide, contributing to significant healthcare spending in both developed and developing countries. Veterans are disproportionately affected by HTN, potentially owing to exposure to active combat, a risk factor specific to this population. However, the most recent review of existing treatment approaches for HTN in this population was conducted in 2014 and addressed only behavioral interventions. We aim to examine existing pharmacological and nonpharmacological interventions to improve HTN control or blood pressure measures among veterans. Methods This is the protocol for a systematic review that will examine existing pharmacological and nonpharmacological interventions (i.e., lifestyle modifications and psychological and psychosocial interventions) to improve HTN control or blood pressure measures among veterans. Our systematic review will follow the Joanna Briggs Institute Manual for Evidence Synthesis, searching four databases (Embase, MEDLINE, Cochrane, and PsycINFO) for eligible studies. The risk of bias will be assessed using the Mixed Methods Appraisal Tool (MMAT) version 2018, followed by content analysis with narrative synthesis to classify and describe the associated interventions and outcomes. Discussion Although we expect to identify gaps in the literature, the findings from this review may guide further research on veteran health and help establish treatment guidelines for this population. This review is one of the few focusing on the veteran population and encompassing both pharmacological and nonpharmacological approaches to treating HTN. It is also the first review on the topic conducted in the last 10 years. Systematic review registration: PROSPERO CRD42024579112.